Tacit Narratives in the Manuscript Collections of Matthew Parker and Robert Cotton - MacNeil, Heather (Archivaria)

(untitled) (Association of Canadian Archivists, 2023)
Over the past two decades, the history of early modern archives has been a topic of considerable interest among historians, and their research has drawn attention to the complex motives and commitments that inspired individuals, communities, and institutions to create, collect, preserve, and use archives in the early modern period. Their research also offers insights into what Eric Ketelaar has called the “tacit narratives of power and knowledge” woven into the formation, preservation, and use of archives and opens up new avenues for exploring the social history of archives. The English Protestant Reformation has provided the backdrop for some of this work, highlighting the ways in which post-Reformation libraries functioned as “polemical weapons” in political and religious struggles to control the historical narrative about the roots of the Reformation. The libraries built by the antiquarian collectors Matthew Parker and Robert Cotton in the 16th and 17th centuries furnish useful examples of the kinds of tacit narratives embedded in the selection, preservation, and use of post-Reformation manuscript collections. This article draws on the research undertaken by early modern historians into the collecting and compiling practices underpinning the formation and use of the Parker and Cotton manuscript collections to demonstrate how their work is helping to illuminate the tacit narratives embedded in early modern archives as well as broadening and deepening the social history of archives.